O capital intelectual como componente do valor patrimonial das organizações - Romante Ezer Ferreira Rodrigues (2014)
This article aims to comprehend the concept of intellectual capital by scholars researching point of view, as well, as how such concept presents itself as a component of patrimonial value within organizations. The intellectual capital has been measured through the Value Added Intellectual Coefficient Method (VAIC), which was chosen after Chagas et al. (2010) for using data published in the organizations balance sheets. The relationship between the intellectual capital of organizations and the return over assets (ROA) has been too verified. Our results indicate that using the VAICTM index may orientate the financial performance of these organizations and that the intellectual capital may be identified as a component of its patrimonial value. This study researched the organizations ranked in the Greatest and Best list of Exame magazine (2013) for the year 2012. Based upon the literature on the subject, this research helped understand the definition of intellectual capital as well as how it participates in the organizations generation of patrimonial value capacity. It was possible, too, to test the methodology and data according as it has been globally found. For the past few centuries researchers have been developing studies with the intention of presenting forms of identification and metrics for calculating intangible assets or intellectual capital and its capacity for generating patrimonial value for organizations. From the investors point of view, patrimonial value consists in an activity which requires careful evaluation and simultaneous indicators in a structured way, allowing to identify the factors that show the investments returns. A total of 1250 business enterprises were studied, from which 52 were selected for matching the criteria for this research. This study concentrates in 15 of these firms, all of which are in the auto-industry business. A quantic-qualitative research has been conducted involving multi-case exploratory research, calculating the Value Added Intellectual Coefficient (VAIC), survey and interviews.